Blockchain Technology Overview: A Novel Approach - Amos R; Anakh K. A; Chandana M. (New Visions in Science and Technology Vol. 7, 2021)
The most important property or feature of Blockchain is that once data is recorded inside a Blockchain, it becomes extremely difficult or impossible to change it. The Blockchain architecture is not so trivial and many have written good articles, tutorials including several videos. Blockchain has many variations depending on how they are configured. The information stored on the blocks and activities performed by various individuals on the networks of Blockchain can be controlled with these variations. the world has found applications of Blockchain technology in several industries, where the trust without the involvement of a centralized authority is desired. So welcome to the world of Blockchain.